Differential photometry of EK DRA and 29 DRA - Zboril M. (Serbian Astronomical Journal, 2005)
We report on BVR precise photometry of active late-type stars EK DRA and 29 DRA in the spring of 2004. The analysis suggests a reasonable fit with single spot model for both cases in the season as far as the V-curve is concerned. The spots are generally cooler than surrounding photosphere and are at high latitudes. The maximal brightness changes for both stars implying a non-rotating component of activity signatures, the spots. We expect that the spot configuration is stable over the period of approximately three months. .